No Words Can’t Describe: Image and Text Relationship between The Title Slate and Content of Netflix’s Ice Cold - Lu'lu'a, Lu'lu'a; Asysyamil, Muhammad Fikri; Zain, Ahsan (Program Studi Sastra Inggris Universitas Jenderal Soedirman, 2024)
The case of Jessica Wongso and the cyanide coffee has become the subject of public debate again since the success of the documentary Ice Cold: Coffee, Murder, and Jessica Wongso by Rob Sixsmith went viral. One of the iconic scenes in the film is the title slate depicting a cup of coffee with blood, which plays a strategic role in framing the narrative and enhancing the film's appeal as a medium for shaping public opinion. This research explored the relationship between the images and text in the title of a documentary film about a criminal case and trial chronology. The research method was qualitative, aiming to understand and describe the complexity of the phenomenon in-depth. This research used Dormehl’s theory (2012) to analyze documentary film types, namely realism and reconstruction, as well as theory of the relationship between image and text to analyze elements in the title slate and text, namely little, close, and beyond in the film by Marsh & White (2003). Six elements were found in the title slate: ‘blood’, ‘glass’, ‘ice’, ‘coffee’, ‘coffee seeds’, and ‘sugar’. The research results indicate that the realism-close relationship was dominant in the data findings. This proved that documentary films can represent reality, and the elements in the title slate represent the overall content of the film. This study can serve as a reference for researching title slates, especially in the context of documentary films.